Answer:
p = 0, p = 12
Explanation:
Given a quadratic equation in standard form
ax² + bx + c = 0 then the nature of its roots is given by the discriminant
Δ = b² - 4ac
For equal roots b² - 4ac = 0
Given
x² -(p - 2)x + 2p + 1 = 0 ← in standard form
with a = 1, b = - (p - 2), c = 2p + 1, then
[- (p - 2)]² - (4 × 1 × 2p + 1) = 0
(p - 2)² - 4(2p + 1) = 0
p² - 4p + 4 - 8p - 4 = 0
p² - 12p = 0 ← factor out p from each term
p(p - 12) = 0
Equate each factor to zero and solve for x
p = 0
p - 12 = 0 ⇒ p = 12